Relationships between total alkalinity in surface water and sea surface dynamic height in the Pacific Ocean. Issue 5 (12th May 2014) - Takatani, Yusuke; Enyo, Kazutaka; Iida, Yosuke; Kojima, Atsushi; Nakano, Toshiya; Sasano, Daisuke; Kosugi, Naohiro; Midorikawa, Takashi; Suzuki, Toru; Ishii, Masao
Abstract Improved spatial and temporal representation of total alkalinity (TA) is expected to be an important component in monitoring changes in the oceanic carbon cycle and acidification over the coming decades. For this reason, previous authors have sought to develop and apply empirical methods to characterize TA in the surface ocean. However, there are regions such as the North Pacific that have proven difficult to successfully represent through empirical relationships based on temperature and salinity with linear regression. Here we propose a new empirical approach for reconstructing TA for the Pacific basin using sea surface salinity and sea surface dynamic height (SSDH). We propose five zones of the Pacific basin where the empirical relationships are applied separately. The root‐mean‐square error of the fittings of these equations to the measured TA is 7.8 μmol kg−1. The SSDH‐based empirical equation helps especially to represent the TA in the North Pacific subtropical‐subarctic frontal zone where salinity‐normalized TA as well as other oceanographic variables exhibits a large meridional gradient and sizeable formation of Central Mode Water and Subtropical Mode Water occurs.